Proceedings of the 2007 ACM Symposium on Applied Computing 2007
DOI: 10.1145/1244002.1244251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of interval-based dynamic voltage scaling algorithms on mobile Linux system

Abstract: During the last several years, dynamic voltage scaling (DVS) algorithms are being used for energy consumption on real, fully functional battery supplied devices, adjusting the clock speed and supply voltage dynamically. Most DVS algorithms are investigated in interval-based and task-based strategies. Taskbased algorithms consider task information, especially task deadline, on deciding what speed to choose at any given time.Interval-based algorithms predict the CPU speed of the upcoming interval based on observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Past research have found that the power consumed by a CPU during operation is linear to the CPU clock frequency [1], [5], [6]. Simulation based power measurement prediction assumes that the CPU power consumption is calculated as the cube of frequency, which do not take into account the processor's idle power requirement [1].…”
Section: Power Estimation and Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research have found that the power consumed by a CPU during operation is linear to the CPU clock frequency [1], [5], [6]. Simulation based power measurement prediction assumes that the CPU power consumption is calculated as the cube of frequency, which do not take into account the processor's idle power requirement [1].…”
Section: Power Estimation and Predictionmentioning
confidence: 99%
“…According to the equation, reduction in the clock frequency will greatly affect the active power. Another generally used equation to predict CPU power consumption comes in the form of CMOS power usage equation [6], [7], [8], [9], [10], [11]. The equation is given below:…”
Section: Power Estimation and Predictionmentioning
confidence: 99%
“…Such a technology is particularly beneficial for embedded systems mainly because of the power constraints and heat dissipation reduction that allow for better use of the available power [4]. The concept of reduced power consumption in an embedded system especially battery power devices are categorized as more important than their fixed power system with access to wall power [1].…”
Section: Dynamic Voltage and Frequency Scalingmentioning
confidence: 99%
“…Linux is fast becoming a major player in the embedded devices platform. With projections from research firms suggesting that shipping of Internet connected devices and Internet of Things (IOT) embedded devices surpassing the shipment of personal computers and smartphones, it is more imperative that maximum energy efficiency are extracted from the devices so that operational time of the devices are prolonged [1].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous work in this area has focused on the use of techniques like gating [1,28,16,11], voltage and frequency scaling [27,14,22,2,26,32,19,29,39], or heterogeneity [13,23] to reduce processor power consumption. These approaches usually target average power dissipation for uniprocessors or chip multiprocessor architectures with a small number of cores.…”
Section: Related Workmentioning
confidence: 99%